2020
DOI: 10.1088/1748-605x/ab6b31
|View full text |Cite
|
Sign up to set email alerts
|

A two-compartment bone tumor model to investigate interactions between healthy and tumor cells

Abstract: We produced a novel three-dimensional (3D) bone tumor model (BTM) to study the interactions between healthy and tumor cells in a tumor microenvironment, the migration tendency of the tumor cells, and the efficacy of an anticancer drug, Doxorubicin, on the cancer cells. The model consisted of two compartments: (a) a healthy bone tissue mimic, made of poly(lactic acid-co-glycolic acid) (PLGA)/beta-tricalcium phosphate (β-TCP) sponge seeded with human fetal osteoblastic cells (hFOB) and human umbilical vein endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
“…Compartmentalised culture models were developed in two studies to enhance OS-healthy cell crosstalk to closely mimic the natural tumour microenvironment. Komez et al (2020) developed a 3D model with two compartments: (1) a bone compartment composed of PLGA/TCL sponges seeded with hFOB and HUVECs and (2) a tumour compartment composed of collagen sponge seeded with Saos-2 OS cells [ 37 ]. This model investigated tumour–bone crosstalk by assessing HUVEC migration from normal bone to tumour compartment via showing increased angiogenic vascular endothelial growth factor (VEGF), fibroblast GF, and IL-8 within the tumour component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward the effort of developing in vitro OS experimental models with improved physiological relevance, a few recent studies have reported 3D OS models using spheroids, [19] nanoporous hydrogels, [20,21] or macroporous scaffolds originally developed for bone tissue engineering. [22][23][24][25][26][27] While these studies suggest the benefits of 3D models over 2D culture, they rely on only a few well-established cell lines that have been passaged in 2D culture for decades and may therefore no longer reflect the biology and heterogeneity of the disease. Furthermore, evaluation was limited mostly to cell proliferation and morphology with only a few markers related to stemness, osteogenesis, or angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] A few studies utilized collagen and hydroxyapatite-containing scaffolds to culture OS cells in vitro. [22][23][24][25] However, the specific role of bone mineral on OS biology and drug response has never been evaluated. Furthermore, the potential of integrating scalable and physiologically relevant 3D OS models with high-throughput sequencing tools for comprehensive interrogation of OS pathology or for identifying potential novel druggable targets remains untapped.…”
Section: Introductionmentioning
confidence: 99%